2010
DOI: 10.3113/fai.2010.0662
|View full text |Cite
|
Sign up to set email alerts
|

Is it Necessary to Re-Fuse a Non-Union of a Hallux Metatarsophalangeal Joint Arthrodesis?

Abstract: Removal of hardware alone is a reasonable option to offer as a relatively minor procedure following a failed arthrodesis of the first MTPJ. This must be accepted on the proviso that in this study four out of 11 (36%) patients proceeded to a revision first MTPJ fusion or first MTPJ replacement. We also found that the rate of non-union in primary first MTPJ fusion was significantly higher in males and those patients who had undergone previous surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Hope et al (2010) described acceptable outcome scores with only removal of material and debridement in 7 of 11 patients. In our series, the 2 patients with hardware failure did not want further treatment, which confirms that some patients tolerate a non-union well.…”
Section: Discussionmentioning
confidence: 95%
“…Hope et al (2010) described acceptable outcome scores with only removal of material and debridement in 7 of 11 patients. In our series, the 2 patients with hardware failure did not want further treatment, which confirms that some patients tolerate a non-union well.…”
Section: Discussionmentioning
confidence: 95%
“…In a level III retrospective study of failed hallux MTPJ arthrodeses, Hope et al showed significantly higher nonunion rates in patients who had undergone previous surgery. 42 Easley et al similarly showed that a previous attempt at subtalar arthrodesis is a significant predictor of nonunion in their level IV retrospective review. 26 Overall, there is fair evidence (grade B recommendation) to implicate soft tissue injury as a risk factor for nonunion.…”
Section: Soft Tissue Injurymentioning
confidence: 96%
“…Hardware removal combined with debridement is another reasonable option. 5,17 There are various publications on risk factors for nonunion after first MTPJ arthrodesis, 8,32,33 albeit with much heterogeneity in terms of patient population and treatment. 20,26 Hence this study aimed to determine the potential association of patient factors, joint preparation, joint fixation, joint positioning, and postoperative immobilization on the incidence of nonunion.…”
Section: Introductionmentioning
confidence: 99%